Energy Transition and Sustainable Development at the Level of the European Union - Daniela Vîrjan; Claudia Rodica Popescu; Iuliana Pop; Delia Popescu (Amfiteatru Economic, 2023)
The energy transition is a priority for the European Union, both in terms of reducing greenhouse gas emissions and reducing its dependence on imported fossil fuels. The European Union is at the forefront of the fight against climate change caused by greenhouse gas emissions. This article presents the relationship between greenhouse gas emissions and the main factors that directly affect the growth of greenhouse gas emissions, such as GDP per capita or greenhouse gas emissions per capita in the previous period (t-1). To conduct this study, a panel data model was used with statistical data provided by EUROSTAT for the 27 Member States of the European Union for the period 2005-2020. Data processing was performed using the econometric program Eviews 8. The research results show that in developed countries, where GDP per capita is high, greenhouse gas emissions are also high. Therefore, the energy transition is a necessity, especially since these countries also have the financial resources to support it.
Keywords: O13; O44; Q01; Q42; Q51; Q53; 330; energy transition; greenhouse gas emissions; green energy; sustainable development; European Union.